2021
DOI: 10.5194/esurf-9-333-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress history on sediment transport and channel adjustment in graded gravel-bed rivers

Abstract: Abstract. With the increasing attention on environmental flow management for the maintenance of habitat diversity and ecosystem health of mountain gravel-bed rivers, much interest has been paid to how inter-flood low flow can affect gravel-bed river morphodynamics during subsequent flood events. Previous research has found that antecedent conditioning flow can lead to an increase in critical shear stress and a reduction in sediment transport rate during a subsequent flood. However, how long this effect can las… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The light table underestimated D 10L by 20% on average and D 90L by 30% on average, with D 10L being the diameter such that 10% of the bedload sediment is finer. For further details on bedload transport measurements, we refer to Zimmermann et al (2008) and An et al (2021). Every 20 min, we calibrated the light table estimated mass and grain size against those measured in the bedload trap.…”
Section: Experimental Design Methodology and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The light table underestimated D 10L by 20% on average and D 90L by 30% on average, with D 10L being the diameter such that 10% of the bedload sediment is finer. For further details on bedload transport measurements, we refer to Zimmermann et al (2008) and An et al (2021). Every 20 min, we calibrated the light table estimated mass and grain size against those measured in the bedload trap.…”
Section: Experimental Design Methodology and Datamentioning
confidence: 99%
“…The light table can detect grains as small as 1 mm. An et al (2021) reported that the median bedload size (D 50L ) show that the light table overestimated D 50L by 3% on average (the subscript "L" denotes load). The light table underestimated D 10L by 20% on average and D 90L by 30% on average, with D 10L being the diameter such that 10% of the bedload sediment is finer.…”
Section: Experimental Design Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Bray, 1971), the Wolman method has been especially popular in the field due to the limited equipment required and its benefit of reducing sampling times whilst providing a relatively valid estimation of reach-scale grain-size distribution. Since then, various versions of the Wolman method were proposed with different approaches to collecting stones such as the random walk approach for particle collection (Leopold, 1970), superimposing gravel templates upon the sedimentological unit for reduced operator error (Bunte and Abt, 2001), and image-based Wolman method analysis (Hassan et al, 2020;An et al, 2021).…”
Section: Introductionmentioning
confidence: 99%